LANGKAH HUKUM PIHAK YANG DIRUGIKAN AKIBAT PERJANJIAN JUAL-BELI ONLINE MELALUI REKENING BERSAMA DENGAN SALAH SATU PIHAK ANAK DI BAWAH UMUR - Lestari Dewi Savitri; Pujiyono Pujiyono (Jurnal Privat Law, 2026)
This article aims to find out the legal steps that can be taken by the relevant party who is harmed by the existence of e-commerce agreements through an escrow with one of the minor subjects. The research methods used are normative juridical, research approaches through legislation, and with data analysis techniques that are deduction by syllogism methods. According to the results of the study, e-commerce activities have been protected by the Law No. 11 of 2008 on Electronic Information and Law No. 8 of 1999 on Consumer Protection. In addition to regulating legal protection of consumers also regulates how the responsibility of business actors if consumers experience losses. One of the legal protections is the arrangement of legal steps to resolve disputes. Legal steps that can be taken by relevant parties who are harmed by the existence of an e-commerce agreement through an escrow with one of the subject minors can be done through litigation and non-litigation.